SOCIOLINGUISTIC FEATURES OF BILINGUALISM IN UZBEK AND ENGLISH: HISTORICAL TRENDS AND CONTEMPORARY PERSPECTIVES - Tursunova Matluba Xolmatovna (Bright Mind Publishing, 2025)
Bilingualism, the ability to use two languages proficiently, has been a subject of linguistic, cognitive, and social research for decades. Historically, bilingualism has been viewed differently depending on sociopolitical contexts, with attitudes ranging from its promotion in multicultural societies to its suppression in monolingual nationalistic states. Contemporary research highlights cognitive benefits, socio-economic advantages, and educational challenges associated with bilingualism. This paper analyzes historical trends, modern perspectives, and implications for language policy and education.
Keywords: Bilingualism, phenomenon, suppression, perspectives, historical, contemporary.